Prediction of A-Level performance from past performance and teachers' estimates - Leo-Rhynie, Elsa
The relationships existing between performance in separate subject areas in the Cambridge A'Level examinations and past performance (PP) in Cambridge O'Level, and Caribbean Examinations Council (CXC) General Level examinations, on the one hand, and teacher estimates (TE) on the other, formed the main focus of this study. TE were, on the whole, better predictors of A'Level performance than PP, and were more reliable for girls than boys in art subjects, and for boys than girls in the sciences. Although the correlations between A'Level and both PP and TE were, for the most part, highly significant, there was a strong tendency in most schools and subject areas for teachers to overestimate students' grades. Implications of these findings for sixth form education are discussed
Keywords: Cambridge GCE A'Level examinations